2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090645
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability analysis for arterial hypertension etiological diagnosis during surgical procedures under tourniquet

Abstract: Pneumatic tourniquets are widely used to provide a bloodless operative field during upper or lower limb surgery. If tourniquet inflation during general anesthesia is initially a mild stimulus, a long duration of inflation can imply heart rate and blood pressure increasing. However, heart rate or blood pressure increasing can also be caused by other external stimuli. Indeed, in the case of an insufficient analgesia, painful surgical stimuli can also cause an increase in heart rate and blood pressure. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…The ANI has been shown to potentially be of value in predicting an imminent haemodynamic stress reaction, 6 and it has also been described to predict treatment success for tourniquet-related hypertension. 10 Under general anaesthesia with desflurane and remifentanil, ANI was found to be more reactive than skin conductance monitoring to different levels of remifentanil infusions in children. 11 The latter suggests that different monitors are not simply exchangeable, even though they may also be based on the assessment of autonomic responses to acute pain/nociception.…”
Section: Discussionmentioning
confidence: 90%
“…The ANI has been shown to potentially be of value in predicting an imminent haemodynamic stress reaction, 6 and it has also been described to predict treatment success for tourniquet-related hypertension. 10 Under general anaesthesia with desflurane and remifentanil, ANI was found to be more reactive than skin conductance monitoring to different levels of remifentanil infusions in children. 11 The latter suggests that different monitors are not simply exchangeable, even though they may also be based on the assessment of autonomic responses to acute pain/nociception.…”
Section: Discussionmentioning
confidence: 90%
“…The main drawback of methods "2" and "3" is the use of data only from the sympathetic component of the ANS, which is also influenced by other physiological factors [18,26].…”
Section: ) Plethysmography Methodsmentioning
confidence: 99%
“…The ANI ability for the analgesia / nociception balance evaluation has been established during a large number of clinical validations [9,11,12,13] which showed that the index was able to detect noxious stimulus with increase sensitivity and specificity than usual clinical parameters (Arterial Blood Pressure and Heart Rate). Furthermore, we showed that, in case of insufficient analgesia, ANI decreases 10 minutes before the occurrence of hemodynamic impairment [13,14].…”
Section: Introductionmentioning
confidence: 94%